Mediação e intervenção social nos conflitos de família - Micheli, Michela Patrícia (2021)
The work aims to show in which context and in what way family mediation works through intervention techniques in family conflicts. The research was carried out at the Mediation Center of the Regional Secretariat IV, which is part of the Mediation Centers of the City Hall of Fortaleza. The object of this work is family mediation and how mediators intervene throughout the process. The paths taken by family conflicts and the experiences experienced during the consultations and mediation sessions by those involved in the conflict were analyzed, through participant observation. The concept of mediation and its historical trajectory in the city of Fortaleza were considered a relevant methodological tool for research, due to the need for immediate intervention and the construction of alternatives in the city of Fortaleza to access justice The bibliographical research included the historical elements mediation, access to justice, conflicts and their institutional approaches. The research also focused on the training of the Mediator and on the native words used in the mediation, including statements from mediators and speeches from the social actors involved in the conflict, during the consultations. Finally, the importance of Nonviolent Communication for Mediation was analyzed.